Growth and Maintenance of Barramundi (Lates calcarifer) Fed with Commercial Feed at BPBAP Situbondo (Indonesian Journal of Aquaculture Medium, 2025)
This study evaluated the growth performance and maintenance of white seabass (Lates calcarifer) fed with commercial feed at BPBAP Situbondo. As a high-value aquaculture commodity with increasing market demand, white seabass farming faces challenges in seed production and growth optimization. The research monitored growth parameters, survival rate (SR), and water quality during a 4-month rearing period (February-June 2024) in concrete tanks (2.5×4×1.2 m). Results showed that commercial feeds (Megami/Skretting) administered via ad-satiation method (3-4x/day for juveniles